Crystal Structure, Electrical Properties, and Energy Storage Capacity of STCN Modified BNT-BKT Based Lead-Free Dielectrics. (19th August 2021) - Rao, Rongrong; Liu, Xiao; Wang, Yiyi; Shi, Jing; Zhao, Yunxia; Zhang, Tao; Du, Huiling
Abstract : Perovskite solid solutions of SrTi(Cu1/3 Nb2/3 )O3 (STCN) modified 0.8Bi0.5 Na0.5 TiO3 −0.2Bi0.5 K0.5 TiO3 (BNT-BKT) in the vicinity of morphotropic phase boundary composition were prepared. The dielectric and impedance properties associated with their structural evolution were investigated. Strong unsteadiness and large hysteresis (dielectric loss) under elevated temperature and variational frequency restrict the development of BNT-BKT based ceramics. Here we show a distinct phase transition from ferroelectric to ergodic relaxor phase that occurs with increasing STCN. Incremental chemical defects resulted from the substitution of the A/B site facilitate the distributions of polar nanoregions. The flatter and smoother dielectric curves between T s and T m illustrate good temperature stability. The complex impedance spectrums demonstrate that the compositions possess a mixed electronic and ionic conduction mechanism. More oxygen vacancies can be introduced into the lattice, contributing to a decremental impedance as the increased dopant. Meanwhile, N b T i will suppress p -type conduction and reduce dielectric loss. Favorable stabilities of dielectric permittivity, energy storage, and electrostrictive strain were achieved, attributed to the existence of nanodomains.